Pengaruh Social Influence dan Self-efficacy Terhadap Intention to Use Mobile Payment System Pada Pengguna E-wallet - Siti Asgina Fauziah; Siti Ashfiasari (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
This study aims to find out the influence of social influence and self-efficacy on the intention to use mobile payment in Sukabumi, especially in the millennial generation. The millennial generation is the generation that has the largest population in Sukabumi and the generation that is the fastest to adapt to emerging modern technology. This study uses quantitative methods with data collection techniques using questionnaires. The data obtained were processed and analyzed by multiple linear regression testing with a total sample of 101 respondent. The results obtained from this study prove that there is a significant influence on social influence and self-efficacy on the intention to use mobile payment either simultaneously or partially. The results of this study are expected to be a reference for interested parties on the topic raised.